2017
DOI: 10.1177/0146167217703064
|View full text |Cite
|
Sign up to set email alerts
|

Media Violence and Other Aggression Risk Factors in Seven Nations

Abstract: Cultural generality versus specificity of media violence effects on aggression was examined in seven countries (Australia, China, Croatia, Germany, Japan, Romania, the United States). Participants reported aggressive behaviors, media use habits, and several other known risk and protective factors for aggression. Across nations, exposure to violent screen media was positively associated with aggression. This effect was partially mediated by aggressive cognitions and empathy. The media violence effect on aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 64 publications
(88 reference statements)
11
51
0
4
Order By: Relevance
“…Overall, cartoon manipulation affects aggressive behaviors through aggressive thoughts, which confirmed prior findings (e.g., Anderson et al, ; Bushman, ). Furthermore, reducing the aggressive thoughts in females in the nonviolent cartoon (natural) condition should be emphasized.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, cartoon manipulation affects aggressive behaviors through aggressive thoughts, which confirmed prior findings (e.g., Anderson et al, ; Bushman, ). Furthermore, reducing the aggressive thoughts in females in the nonviolent cartoon (natural) condition should be emphasized.…”
Section: Discussionsupporting
confidence: 88%
“…Some researchers, on the other hand, asserted that there is no valid evidence to confirm the positive links between media violence and aggression (e.g., Ferguson & Dyck, ; Ferguson & Kilburn, ; Freedman, ; Hilgard, Engelhardt, & Rouder, ; Holden, ). In our view, the evidence is overwhelming that media violence increases aggression (see Anderson et al, ; Greitemeyer & Mügge, ). Therefore, the debate should not be about whether there is an effect or not, but how the effect is mediated and who is most likely to be affected.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The standardized regression weights vary between 0.10 and 0.20, which implies that the class level has a small‐ to medium‐sized effect on the development of aggression. Because aggression is caused by a multitude of factor, this finding is in line with other risk factors for aggression (e.g., Anderson et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Exposure to violent media is a cause of aggressive behavior and is correlated with violent criminal behavior (Bushman & Anderson, ), including mass shootings (O'Toole, ). It is important to note that the link between violent media and aggression is found in every country where studies have been conducted (Anderson et al, , ). A number of long‐term studies have also found that high exposure to violent media in childhood is related to violence later in life, including criminal behavior, spousal abuse, and assault (Huesmann, Moise‐Titus, Podolski, & Eron, ).…”
Section: Environmental Risk Factors For Youth Violencementioning
confidence: 99%